Climate Policies of G20 and New Threats for Russian Energy and Transportation Complex - Iosifov, Valeriy V.; Ratner, Pavel D. (International Journal of Energy Economics and Policy, 2020)
The aim of this study is tracking the goals of national climate policies and real trends in the carbon intensity of the economies of the G20 countries. A comparative content analysis of the Intended Nationally Determined Contributions (INDC) of the G20 countries was performed. The trends of mean were built for the carbon intensity indicator of G20 countries in the period 1991-2014. The countries, which already passed the peak of the carbon intensity of the economy, were identified. The constructed models of time series of carbon intensity can be used to forecast the future dynamics of the carbon intensity of the G20 countries and to estimate the changes in the world’s hydrocarbons demand. The issues of global energy security from the perspective of energy resources exporters were discussed. Keywords: climate strategies, G20, carbon intensity, global energy security, energy transition JEL Classifications: O33, Q42, Q47, Q48 DOI: https://doi.org/10.32479/ijeep.10432